Associations of objectively assessed physical activity and sedentary time with health‐related quality of life among colon cancer survivors. Issue 18 (4th June 2014) - Vallance, Jeff K.; Boyle, Terry; Courneya, Kerry S.; Lynch, Brigid M.
Abstract : BACKGROUND: The primary purpose of this study was to determine associations of accelerometer‐assessed moderate‐ to vigorous‐intensity physical activity (MVPA) and sedentary time with health‐related quality of life (HRQoL) and physical function and well‐being in colon cancer survivors. METHODS: Colon cancer survivors (N = 178) from Alberta, Canada (n = 92) and Western Australia (n = 86) completed a mailed survey that assessed HRQoL (Functional Assessment of Cancer Therapy–Colorectal), physical function and well‐being (Trial Outcome Index–Colorectal), and relevant covariates. MVPA and sedentary time were assessed using the Actigraph GT3X+ accelerometer (60‐second epochs) via a 7‐day monitoring protocol. Average daily MVPA and sedentary time was corrected for wear time and then examined as quartiles. RESULTS: Adjusting for relevant demographic, behavioral, and clinical covariates, a significant difference in HRQoL scores emerged between quartile 1 (Q1) and Q4 (Mdiff  = 11.5, P  = .038). For physical function and well‐being, a significant difference emerged between Q1 and Q4 (Mdiff  = 9.1, P  = .009). For fatigue, a significant difference emerged between Q1 and Q4 (Mdiff  = 7.1, P  = .05). Significant differences were also observed for between Q1 and Q3 (Mdiff  = 2.4, P  = .041), and Q1 and Q4 (Mdiff  = 3.5, P  = .002) for colorectal cancer–specific symptoms. There were no statistically significant associations of sedentary time with HRQoL, physical function and well‐being, fatigue, or colorectal cancer–specific symptoms. CONCLUSIONS: Objectively measured MVPA, but not sedentary time, was associated with better HRQoL, physical function and well‐being, and colorectal cancer–specific symptoms in colon cancer survivors. For MVPA, differences met or exceeded contemporary cutpoints for determining clinically important differences. Cancer 2014;120:2919–2926. © 2014 American Cancer Society . Abstract : This study is one of the first to demonstrate significant and meaningful associations of objectively assessed physical activity with health‐related quality of life and fatigue among cancer survivors. Associations were not observed for sedentary time.